CELEBRITY ENDORSER, PRICE DISCOUNT DAN PRODUCT QUALITY TERHADAP MINAT BELI PRODUK ORIFLAME - Feby Evelyna (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to analyze the effect of celebrity endorsers, price discounts and product quality on the buying interest Oriflame products (Studies in the Community of Kebumen Regency). Data collection was carried out using a questionnaire, using a Likert scale of 4. This study took 100 respondents. The method used is purposive sampling. The hypothesis was tested using multiple linear regression analysis with the help of the SPSS 25 for windows program. The results showed that celebrity endorsers had an effect on the buying interest Oriflame products, price discounts did not affect the intention to buy Oriflame products, product quality had an effect on the buying interest Oriflame products. Celebrity endorsers, price discounts and product quality have a significant effect simultaneously (together) on the buying interest Oriflame products